2012
DOI: 10.1111/j.1438-8677.2011.00534.x
|View full text |Cite
|
Sign up to set email alerts
|

Litter mixture effects on tropical tree seedling growth – a greenhouse experiment

Abstract: Decomposing litter provides critical nutrients for plants, particularly in nutrient-poor ecosystems such as tropical forests. We hypothesised that decomposing litter improves the performance of a variety of tropical tree seedlings, and that this litter effect varies depending on the species of litter present in litter mixtures. We addressed these hypotheses with a large pot experiment manipulating a range of different litter mixtures of contrasting quality and using seedlings of four tree species from the Amaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 70 publications
1
5
1
3
Order By: Relevance
“…In Borneo, Brearley et al (2003) found that mixing leaf litter into pots of soil improved the growth of seedlings from three species of dipterocarp tree, and that this positive response was associated with increased nutrient availability to seedlings. In contrast, in French Guiana Coq et al (2012) found neutral and even negative effects of adding litter to pots of soil on the growth of seedlings from four species of tree. The authors proposed toxic effects of litter and enhancement of fungal pathogens amongst possible explanations for the lack of a positive effect of litter on seedling growth.…”
Section: Introductionmentioning
confidence: 92%
“…In Borneo, Brearley et al (2003) found that mixing leaf litter into pots of soil improved the growth of seedlings from three species of dipterocarp tree, and that this positive response was associated with increased nutrient availability to seedlings. In contrast, in French Guiana Coq et al (2012) found neutral and even negative effects of adding litter to pots of soil on the growth of seedlings from four species of tree. The authors proposed toxic effects of litter and enhancement of fungal pathogens amongst possible explanations for the lack of a positive effect of litter on seedling growth.…”
Section: Introductionmentioning
confidence: 92%
“…During seedling establishment in forests, early root growth and proliferation often occur in the litter layer. Few studies have investigated whether and how such processes are affected by litter type, in terms of litter species identity and decomposition stage (Coq et al , Lopez‐Iglesias et al , Bonanomi et al ). In this study, we combine litter characterization by proximate analyses, a widely used technique for compositional analysis of C pools (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…(ii) De acordo com a hipótese do Home Field Advantage, a interação entre a qualidade de uma serapilheira local e a sua comunidade decompositora provoca a especialização dos organismos do solo que passam a decompor um material vegetal produzido localmente, ao qual estão mais bem adaptados, com maior rapidez em relação a um material externo (GHOLZ et al, 2000;COQ et al, 2012). Dessa forma, devido a ocorrência do HFA, espera-se que a decomposição das espécies vegetais nos seus locais de origem seja maior do que a decomposição de espécies externas introduzidas a partir de outro ambiente, bem como espera-se que a decomposição das espécies vegetais seja maior nos seus locais de origem quando comparada a decomposição destas mesmas espécies em um local externo.…”
Section: Hipótesesunclassified
“…A hipótese do Home Field Advantage define que uma serapilheira será decomposta mais rapidamente na área de influência das espécies vegetais de onde deriva (home) do que sob a influência de outras espécies, sugerindo uma possível adaptação entre plantasdecompositores que resulta em uma maior eficiência na decomposição do material vegetal (GHOLZ et al, 2000;AYRES et al, 2009;MILCU;MANNING, 2011;COQ et al, 2012;GABRIEL-PEREZ et al, 2013;WANG et al, 2013). Sabe-se que esta adaptação ocorre através de interações relacionadas ao momento em que os decompositores necessitam acessar os compostos energéticos e nutrientes contidos na serapilheira adjacente, uma vez que este material consiste na principal fonte de recursos para a biota do solo, que precisa estar apta a degrada-lo (WARDLE; BONNER; NICHOLSON, 1997;NEGRETE-YANKELEVICH et al, 2008;TOWSEND et al, 2008;AYRES et al, 2009;COQ et al, 2011COQ et al, , 2012 No entanto, os mecanismos pelos quais este processo ocorre permanecem elusivos, devido à complexidade e multiplicidade de fatores espaciais e temporais que podem influenciar nas interações de afinidade entre organismos e a serapilheira (AUSTIN et al, 2014;CHOMEL et al, 2015). (CHAPIN III et al, 2002;RAHMAN et al, 2014).…”
Section: A Hipótese Do Home Field Advantageunclassified
See 1 more Smart Citation